The intimate relationship between obesity and poor quality of life in university students (Research, Society and Development, 2022)
Admission to a university presents a major change in the individual's standard of living. The accumulation of academic activities and the frequent stress related to anxiety regarding studies are factors that allow a sedentary lifestyle, inadequate diet and lack of motivation, with consequent weight gain. Thus, the present study aims to present, through a literature review, the impact of obesity on the quality of life of university students. It is an integrative literature review that seeks to raise awareness, recognize and synthesize the production of knowledge about a topic. A search for data was carried out in the Google Scholar, SCIELO and LILACS databases, in Portuguese, using the following descriptors: obesity, quality of life, university student, combined with each other. Studies have shown that social, economic and cultural factors are present in the determination of obesity. Excess weight among university students is related to poor diet, younger age and lower exposure to university, that is, to those who are in their first year. Thus, it is concluded that it is essential that there is a greater incentive in the university environment to practice physical activity and to adopt a healthy lifestyle in order to reduce and avoid obesity so that, on the other hand, there is an increase in quality. of life.